A BIOMECHANICAL EVALUATION OF LIGAMENT AND MUSCULAR STIFFNESS IN THE DISTAL UPPER EXTREMITY - Holmes, WR Michael (My University, 2011)
The purpose of this thesis was to evaluate musculoskeletal contributions to joint stiffness in the distal upper extremity. An in-vitro and in-vivo approach was used to examine muscle and ligament contributions to mechanical joint stiffness at the elbow and wrist. In Chapters 2 and 3 an in-vitro approach was used to evaluate ligament contributions to carpal tunnel mechanics. Chapter 2 documented transverse carpal ligament (TCL) mechanical properties and provided a calculation of TCL length when stretched, which confirmed the ligaments importance in carpal tunnel mechanics and carpal bone stability. Chapter 3 quantified mechanical properties of the TCL at six different locations using a biaxial tensile testing method. It was found that the complex TCL fibre arrangement makes the tissue properties location dependent. The TCL contributes to carpal tunnel mechanics and carpal stability and the ligament contributions are different depending on the tissue location tested. Chapters 4 and 5 focused on the effects of hand loads and arm postures on the muscular response to sudden arm perturbations. The elbow flexors demonstrated stiffness contributions immediately prior to a perturbation and were influenced by posture and hand loading. The forearm muscles provided a small contribution to elbow joint stiffness. Chapter 6 also found muscular contributions that increased wrist joint stiffness immediately prior to a sudden perturbation. Additionally, for a small grip-demanding task, forearm muscle co-contraction resulted in large increases in wrist joint stiffness.
This thesis has provided a detailed analysis of the TCL which improves our understanding of the carpal tunnel and specific mechanisms of injury. It is the first to document individual muscle contributions to elbow and wrist joint stiffness. The comprehensive analysis of ligament and muscular contributions to joint stiffness has provided insight into joint stability in the distal upper extremity. This can improve our understanding of injury caused by sudden joint loading.
Keywords: Distal Upper Extremity; Stability; Muscle Stiffness; Ligament Stiffness; Cadaver; Occupational Biomechanics; Biomechanical Engineering; Biomechanics; Motor Control; Biomechanical Engineering